Solvent type amorphous polymer copolyester as well as preparation method and application thereof

By introducing diols with different side chain substituents into the copolyester, solvent-based amorphous polymer copolyester is synthesized, which solves the problem that the existing copolyester materials are difficult to dissolve in organic solvents and lack of flexibility, and achieves excellent solubility and adhesion properties.

CN119899362APending Publication Date: 2025-04-29EAST CHINA UNIV OF SCI & TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510398308.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-01
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

Existing copolyester materials are limited in coating and bonding applications due to their inability to dissolve in common organic solvents, and are low in flexibility and elongation at break.

Method used

By introducing diols with different side chain substituents as comonomers, the molecular structure of the polymer is adjusted to synthesize solvent-based amorphous polymer copolyesters with excellent solubility, flexibility and high transparency.

Benefits of technology

It has achieved excellent solubility of copolyester in organic solvents such as ketones, esters, and ethers, and has excellent adhesion and gloss. It is suitable for the coating and bonding of substrates such as metals and plastics, and improves the performance of adhesives and film-forming materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899362A_ABST
    Figure CN119899362A_ABST
Patent Text Reader

Abstract

The invention discloses a solvent type amorphous polymer copolyester and a preparation method and application thereof, and belongs to the technical field of polyester synthesis, and fatty alcohol with different side chain structures and carbon chain lengths is added as dihydric alcohol with a methyl-containing side chain for modification. In the feeding stage, the molar ratio of alcohol to acid is controlled to be (1.2-1.6): 1 so as to ensure that the esterification reaction is fully carried out. Different from a traditional method, the excessive alcohol in the method only refers to ethylene glycol. As the boiling point of the ethylene glycol is low, the ethylene glycol is easy to evaporate in the subsequent vacuum polycondensation process, the characteristic is beneficial to promoting the growth of polyester chains, and the actual ratio of alcohol acid is convenient to control. By adopting a multi-component copolymerization technology, the regularity of a polyester molecular chain is broken, the amorphous polyester is successfully synthesized, and the amorphous polyester has excellent solubility and film-forming property. The copolyester has excellent adhesion to metal, plastic and other substrates, and can be independently used as an adhesive or a film-forming substance for coating and bonding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyester synthesis, and in particular relates to a solvent-based amorphous polymer copolyester and a preparation method and application thereof. Background Art

[0003] At present, the copolyesters commonly used in the domestic market mainly include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT) and polyarylate, etc. These semi-crystalline polyesters have excellent heat resistance and mechanical properties. They are usually used as engineering plastics, packaging materials or for fibers and textiles, but are usually insoluble in common organic solvents, which limits their application in coating and bonding.

[0004] A Chinese patent with publication number CN108048940A discloses a soft polyester fiber and a preparation method thereof, wherein adipic acid segments are introduced into the synthesis of PET. Since adipic acid segments are relatively long fatty chains, the introduction of adipic acid segments results in a decrease in the rigidity of the synthesized polyester, an increase in toughness, and an increase in elongation at break. Moreover, the copolyester is poorly soluble in organic solvents and cannot be coated and bonded.

[0005] The Chinese patent with publication number CN117567733A discloses a synthesis method of PETG copolyester and its transparency improvement. The method adds 1,4-cyclohexanedimethanol as the third monomer and mixes and copolymerizes with terephthalic acid, ethylene glycol and a compound catalyst. The synthesis method is simple and easy, the reaction is stable, the conditions are mild, and the preparation can be completed in one step. The PETG copolyester chips synthesized by the patent have high transparency and thermodynamic stability, but the measured elongation at break of the copolyester is low, the flexibility is poor, and it is difficult to dissolve in common organic solvents.

[0006] A Chinese patent with publication number CN119264402A discloses a modified copolyester material, a preparation method and a use thereof. The method copolymerizes by adding 2,2,4,4-tetramethyl-1,3-cyclobutanediol, spirodiol or trimethylolpropane as a modified monomer, so that the modified copolyester material has excellent properties such as high transparency, high toughness, high strength, high modulus and solvent resistance. At the same time, the polyester material is firmly bonded during the hot pressing composite process and is not prone to deformation, delamination and the like. However, the synthesis of the copolyester requires a higher reaction temperature, which increases production energy consumption, and is difficult to dissolve in organic solvents and cannot be coated.

[0007] A Chinese patent with publication number CN114466880A discloses a saturated polyester copolymer and its preparation method and application. The method introduces a component having both an ester ring group and a benzene ring group into the polyester copolymer to achieve an orderly distribution of the space groups in the chain segment, enhance the coupling effect of the steric hindrance group, and improve the adhesion to the plastic substrate. However, the compound structure selected in the patent is relatively complex, the cost is high, the synthesis process is difficult, and it is not conducive to industrial production. Summary of the invention

[0008] In order to solve the above technical problems, the present invention proposes a solvent-based amorphous polymer copolyester and a preparation method and application thereof.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] One of the technical solutions of the present invention:

[0011] The present invention provides a solvent-based amorphous polymer copolyester, the general structural formula of which is as follows:

[0012]

[0013] Wherein, R1, R2 and R3 are independently selected from hydrogen atom (H), methyl group (CH3) or long carbon chain substituent (C z H 2z+1 , z is an integer greater than 1; preferably z is 1 to 4, and z is an integer); m represents the number of repetitions of terephthalic acid-ethylene glycol ester structural units in polyethylene terephthalate copolyesters of different structures; n represents the number of repetitions of linear long-chain dibasic acid and diol polyester structural units with different side chain substituents; x, y, m and n are all integers greater than 1;

[0014] The number average molecular weight (Mn) of the solvent-based amorphous polymer copolyester is 30,000-45,000 Da, and the polymer dispersibility index (PDI) is 1.7-2.0.

[0015] The solvent-based amorphous polymer copolyester (referred to as copolyester) of the present invention has excellent solubility and film-forming properties. The copolyester of the present invention has an amorphous form and exhibits excellent solubility in organic solvents such as ketones, esters, and ethers, and can be used for coating of substrates such as metals, aluminum foils, and plastics. For example, the copolyester of the present invention can be dissolved in solvents such as ethyl acetate, toluene, acetone, cyclohexanone, methyl isobutyl ketone, and N-methylpyrrolidone. The copolyester can be used as a single adhesive or film-forming material for coating and bonding, and exhibits excellent adhesion and glossiness to substrates such as metals and plastics. It can be used for electronic device packaging bonding, for example: in the manufacture of flexible circuit boards (FPCs), by coating copolyester adhesives, effective bonding of plastic substrate films and metal wires is achieved, with both insulation and optical transparency.

[0016] Further, the preparation method of the diol polyester structural unit with different side-chain substituents is as follows: Mix a diol with a methyl group in the side chain and a diacid, and carry out an esterification dehydration reaction at a temperature of 230-240 °C. The reactant is the diol polyester structural unit with different side-chain substituents.

[0017] The second technical solution of the present invention:

[0018] The present invention also provides a preparation method of the above solvent-based amorphous high molecular copolyester, comprising the following steps:

[0019] Charge aromatic dicarboxylic acid, ethylene glycol, diol with a methyl group in the side chain, linear long-chain diacid, polycondensation catalyst and heat stabilizer at one time and mix them. Carry out pretreatment at a temperature of 80 °C under nitrogen protection;

[0020] After the pretreatment, carry out an esterification reaction at a temperature of 230-240 °C;

[0021] After the esterification reaction is completed, keep the reaction temperature unchanged, carry out low-vacuum extraction on the reaction system to make the vacuum degree reach 50 Pa, and keep the temperature at 240 °C. When the reaction system becomes viscous, stop heating. The product is the solvent-based amorphous high molecular copolyester.

[0022] Further, the general structural formula of the linear long-chain diacid is:

[0023]

[0024] Among them, y is an integer greater than 1; preferably 1 < y < 17 and y is an integer.

[0025] Furthermore, the linear long-chain diacid is selected from adipic acid, sebacic acid or C12-C18 diacid, and more preferably adipic acid or sebacic acid. The linear long-chain diacid of the present invention is cheap in price and good in stability.

[0026] Preferably, the reaction time at a temperature of 240 °C is 3-5 h (i.e., the polycondensation reaction time is 3-5 h). The present invention adjusts the molecular weight of the copolyester by controlling the copolymerization reaction duration. Specifically, by reasonably prolonging the polycondensation reaction time, the molecular weight of the copolyester can be effectively increased. The polycondensation reaction is a step-by-step polymerization process. Prolonging the polycondensation reaction time can promote the reaction of more diacids and diols, and at the same time reduce the residue of low-molecular-weight by-products (such as water, alcohol, etc.), thereby promoting the growth of polymer chains and finally obtaining a high-molecular-weight copolyester. The copolyester of the present invention has a high elongation at break and good flexibility. The solvent-based amorphous high molecular copolyester of the present invention can be used as an adhesive or film-forming material for metal substrates.

[0027] The invention adjusts the molecular structure and performance of solvent-based amorphous polymer copolyester by introducing specific comonomers during the synthesis process. Adding diols with side chain substitutions into the polymerization reaction can synthesize resins with good solubility, flexibility and high transparency. The synthesis method of the invention is simple, the raw material cost is low, the process is pollution-free, and the application scope of domestic copolyester synthesis in the field of adhesives is broadened.

[0028] Further, the molar ratio of the alcohol component to the acid component is 1.2 to 1.6:1, preferably 1.5:1;

[0029] And / or, the alcohol component is ethylene glycol and a diol having a methyl group on the side chain;

[0030] And / or, the acid component is an aromatic dicarboxylic acid and a linear long-chain dibasic acid.

[0031] Furthermore, the aromatic dicarboxylic acid is terephthalic acid and isophthalic acid, and the molar ratio is 1-5:1, preferably 2.5:1.

[0032] Furthermore, the general structural formula of the diol containing methyl groups in the side chain is:

[0033]

[0034] Wherein, x is an integer greater than 1, R1, R2 and R3 are independently selected from H, CH3 or a long carbon chain substituent (C z H2 z+1 , z is an integer greater than 1), and at least one of R1, R2 and R3 is CH3.

[0035] Furthermore, the diol containing methyl groups in the side chain is selected from 1,2-propylene glycol ( )、2-methyl-1,3-propanediol( )、1,3-Butanediol( )、2-butyl-2-ethyl-1,3-propanediol( )、neopentyl glycol(NPG, )、2-methyl-2,4-pentanediol( ), 2,2,4-trimethyl-1,3-pentanediol ( ) and 3-methyl-1,5-pentanediol ( ). Preferably, the diol containing methyl groups on the side chain is selected from one of 2-methyl-1,3-propanediol, neopentyl glycol, 3-methyl-1,5-pentanediol and 2-butyl-2-ethyl-1,3-propanediol. The diol containing methyl groups on the side chain of the present invention is cheap and easy to purchase.

[0036] The diol containing methyl groups in the side chain of the present invention contains methyl groups (it can also be referred to as diol containing side methyl groups). The introduction of side methyl groups significantly improves the solubility of the copolyester in organic solvents, which may be because the side methyl groups increase the hydrophobicity of the molecular chain. At the same time, the presence of side methyl groups increases the flexibility and steric hindrance of the molecular chain, and the flexible chain segments are more easily adapted to the microstructure of the substrate surface, thereby improving the adhesion of the copolyester on the substrate.

[0037] Furthermore, the molar proportion of the diol containing methyl groups in the side chain in the alcohol component is 10-40%, and the molar proportion of the ethylene glycol in the alcohol component is 60-90%;

[0038] And / or, the molar proportion of the aromatic dicarboxylic acid in the acid component is 40-80%, and the molar proportion of the linear long-chain dibasic acid in the acid component is 20-60%.

[0039] Different from the conventional method, the excess alcohol in the present invention is only ethylene glycol, which ensures that the alcohol is excessive when feeding, and the molar ratio of hydroxyl group to carboxyl group is greater than 1, thereby ensuring that the esterification reaction is completely carried out. Since ethylene glycol is easy to evaporate in the subsequent polycondensation process, it not only promotes the growth of the polymerization chain, but also can better control the actual ratio of dibasic acid (aromatic dicarboxylic acid and linear long-chain dibasic acid) and diol (ethylene glycol and diol with methyl group in the side chain).

[0040] Furthermore, the amount of the polycondensation catalyst added is 0.05-0.1% of the mass of the linear long-chain dibasic acid;

[0041] And / or, the amount of the heat stabilizer added is 0.05-0.1% of the mass of the linear long-chain dibasic acid.

[0042] Further, the polycondensation catalyst is selected from one of tetrabutyl titanate, antimony ethylene glycol and dibutyltin dilaurate;

[0043] And / or, the heat stabilizer is selected from one of phosphite, triphenyl phosphate, antioxidant 168 and antioxidant 1010.

[0044] Furthermore, during the esterification reaction, a distillation column is used for temperature monitoring, and the column top temperature is set as the system steam temperature, and the system steam temperature is 70°C~105°C. When the reaction system gradually changes from turbid to clear and transparent, it is considered to have reached the clear point of the esterification reaction. When the column top temperature drops below 60°C and the amount of distilled water reaches more than 95% of the theoretical water output, the esterification reaction is terminated.

[0045] The third technical solution of the present invention:

[0046] The present invention also provides the use of the solvent-based amorphous polymer copolyester in the preparation of adhesives or film-forming materials.

[0047] Compared with the prior art, the present invention has the following advantages and technical effects:

[0048] (1) The solvent-based amorphous polymer copolyester of the present invention has excellent solubility and film-forming properties, and exhibits excellent solubility in organic solvents such as ketones, esters, and ethers. It can be used as a single adhesive or film-forming material for coating and bonding, and has excellent adhesion and high transparency to substrates such as metals and plastics.

[0049] (2) The solvent-based amorphous polymer copolyester of the present invention is a saturated polyester resin with a high number average molecular weight (up to 30,000-45,000 Da), and exhibits high tensile strength and elongation at break. The substrate coated with the copolyester can obtain excellent mechanical strength and wear resistance, which can effectively extend the service life of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0051] Figure 1 This is the H-NMR spectrum of the solvent-based amorphous polymer copolyester obtained in Example 2;

[0052] Figure 2 This is the XRD pattern of the solvent-based amorphous polymer copolyester obtained in Example 2. DETAILED DESCRIPTION

[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0054] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0055] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0056] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0057] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0058] The invention provides a polyester modification method, which is modified by adding fatty alcohols with different side chain structures and carbon chain lengths as diols containing methyl groups in the side chains. In the feeding stage, the molar ratio of alcohol to acid is controlled to be 1.2-1.6:1 to ensure that the esterification reaction is fully carried out. Different from the traditional method, the excess alcohol in the present invention refers only to ethylene glycol. Since ethylene glycol has a low boiling point, it is easy to evaporate in the subsequent vacuum polycondensation process. This characteristic helps to promote the growth of the polyester chain and facilitates the control of the actual ratio of alcohol to acid. In addition, the present invention adopts multi-component copolymerization technology to break the regularity of the polyester molecular chain and successfully synthesize amorphous polyester. By regulating the type and length of carbon chain monomers, the influence of carbon chain type and length on the mechanical properties and solubility of polyester is studied, and a polyester material with excellent solubility and film-forming properties is synthesized. The polyester has excellent adhesion to substrates such as metals and plastics, and can be coated and bonded as an adhesive or film-forming material alone.

[0059] The embodiment of the present invention provides a solvent-based amorphous polymer copolyester, the general structural formula of which is as follows:

[0060]

[0061] Wherein, R1, R2 and R3 are independently selected from hydrogen atom (H), methyl group (CH3) or long carbon chain substituent (C z H 2z+1, z is an integer greater than 1; preferably, z is 1 - 4 and z is an integer); m represents the number of repetitions of terephthalic acid - ethylene glycol structural units in copolyesters of polyethylene terephthalate with different structures; n represents the number of repetitions of linear long - chain dibasic acid and dibasic alcohol polyester structural units with different side - chain substituents; x, y, m, and n are all integers greater than 1;

[0062] The number - average molecular weight (Mn) of the solvent - based amorphous polymer copolyester is 30,000 - 45,000 Da, and the polydispersity index (PDI) is 1.7 - 2.0.

[0063] In the examples of the present invention, the preparation method of the dibasic alcohol polyester structural unit with different side - chain substituents is as follows: Mix the dibasic alcohol with a methyl - containing side chain and the dibasic acid, and carry out an esterification dehydration reaction at a temperature of 230 - 240 °C. The reactant is the dibasic alcohol polyester structural unit with different side - chain substituents.

[0064] In the examples of the present invention, the general structural formula of the linear long - chain dibasic acid is:

[0065]

[0066] wherein, y is an integer greater than 1; preferably 1 < y < 17 and y is an integer.

[0067] In some preferred embodiments of the present invention, the linear long - chain dibasic acid is selected from adipic acid, sebacic acid, or C12 - C18 dibasic acid, more preferably adipic acid or sebacic acid. The linear long - chain dibasic acid used in the present invention is inexpensive and has good stability.

[0068] The solvent-based amorphous polymer copolyester (hereinafter referred to as copolyester) of the present invention has excellent solubility and film-forming properties. The copolyester of the present invention has an amorphous form and exhibits excellent solubility in organic solvents such as ketones, esters, and ethers, and can be applied to the coating of substrates such as metals, aluminum foils, and plastics. For example, the copolyester of the present invention can be dissolved in solvents such as ethyl acetate, toluene, acetone, cyclohexanone, methyl isobutyl ketone, and N-methylpyrrolidone. The copolyester can be applied and bonded as a single adhesive or film-forming material, and exhibits excellent adhesion and glossiness to substrates such as metals and plastics. It can be applied to electronic device packaging bonding, for example: in the manufacture of flexible circuit boards (FPCs), the plastic substrate film and the metal wire are effectively bonded by coating the copolyester adhesive, and both electrical insulation and optical transparency are achieved. The reason why the solvent-based amorphous polymer copolyester of the present invention has electrical insulation is: ① The solvent-based amorphous polymer copolyester is a molecular structure dominated by covalent bonds, and its valence electrons are tightly bound between atoms and cannot move freely, resulting in the material being difficult to conduct electricity. ② There are neither free electrons nor mobile ions in the solvent-based amorphous polymer copolyester molecules, and no current path can be formed, so it exhibits excellent electrical insulation.

[0069] An embodiment of the present invention further provides a method for preparing a solvent-based amorphous polymer copolyester, comprising the following steps:

[0070] (1) Preprocessing stage

[0071] Aromatic dicarboxylic acid, ethylene glycol, diol with methyl groups on the side chain, linear long-chain dicarboxylic acid, polycondensation catalyst and thermal stabilizer are added and mixed at one time. After the addition is completed, the cold water circulation of the condensation column is started, and the device is purged and replaced with nitrogen (N2) three times, and then the electric heating jacket is turned on for heating, and the temperature is raised to 80°C, and the materials are continuously pre-mixed, wherein the aromatic dicarboxylic acid is terephthalic acid and isophthalic acid; the molar ratio of the alcohol component to the acid component is 1.2-1.6:1, preferably 1.5:1, the alcohol component is ethylene glycol and diol with methyl groups on the side chain, and the acid component is aromatic dicarboxylic acid and linear long-chain dicarboxylic acid; the general structural formula of the diol with methyl groups on the side chain is:

[0072]

[0073] Wherein, R1, R2 and R3 are independently selected from H, CH3 or a long carbon chain substituent (C z H2 z+1 , z is an integer greater than 1), and at least one of R1, R2 and R3 is CH3; the diol containing a methyl group in the side chain is selected from 1,2-propylene glycol ( )、2-methyl-1,3-propanediol( )、1,3-Butanediol( )、2-butyl-2-ethyl-1,3-propanediol( )、neopentyl glycol(NPG, )、2-methyl-2,4-pentanediol( )、2,2,4-trimethyl-1,3-pentanediol( ) and 3-methyl-1,5-pentanediol ( ). Preferably, it is one of 1,2-propylene glycol, 2-methyl-1,3-propylene glycol, neopentyl glycol, 3-methyl-1,5-pentanediol and 2-butyl-2-ethyl-1,3-propylene glycol. The diol with methyl groups in the side chain used in the present invention is cheap and easy to purchase. The introduction of the side methyl groups significantly improves the solubility of the copolyester in organic solvents, which may be because the side methyl groups increase the hydrophobicity of the molecular chain. At the same time, the presence of the side methyl groups increases the flexibility and steric hindrance of the molecular chain, and the flexible chain segments are more easily adapted to the microstructure of the substrate surface, thereby improving the adhesion of the copolyester on the substrate.

[0074] (2) Esterification reaction stage

[0075] The temperature of the heating jacket is gradually raised to 230-240°C (i.e., the esterification reaction temperature is set between 230-240°C), and nitrogen is used to purge to remove water and by-products generated during the reaction. A fractionating column is used to monitor the temperature during the esterification process, and the column top temperature of the thermometer at the outlet of the fractionating column is the system steam temperature, which is maintained between 70°C and 105°C. When the reaction system gradually changes from turbid to clear and transparent, it is considered to have reached the clear point of the esterification reaction. When the column top temperature drops below 60°C and the amount of distilled water reaches more than 95% of the theoretical water output, the esterification reaction is completed.

[0076] (3) Polycondensation reaction stage

[0077] After the esterification reaction is completed, the reaction temperature is maintained constant, and a diaphragm pump and a vacuum oil pump are used to perform low vacuum extraction on the reaction system to prevent the liquid esterification product in the three-necked flask from boiling over. The vacuum degree is gradually increased to 50 Pa, and the temperature of the heating jacket is maintained at 240°C. At the same time, ethylene glycol and oligomers are continuously extracted by a vacuum pump to control the polycondensation reaction time. The preferred polycondensation reaction time is 3 to 5 hours. After the reaction is completed, heating and stirring are stopped, and the vacuum is turned off. The obtained polycondensation product is quickly poured into water while hot to obtain a copolyester product (i.e., a solvent-based amorphous polymer copolyester).

[0078] The present invention can effectively increase the molecular weight of the copolyester by reasonably extending the polycondensation reaction time. The polycondensation reaction is a step-by-step polymerization process. Extending the polycondensation reaction time can promote more dibasic acids and diols to react, while reducing the residual low molecular weight byproducts (such as water, alcohol, etc.), thereby promoting the growth of polymer chains and finally obtaining a high molecular weight copolyester. The copolyester of the present invention has a high elongation at break and good flexibility, meeting the requirements of metal substrate processing and molding.

[0079] In the embodiments of the present invention, the molar proportion of the diol containing methyl groups in the side chain in the alcohol component is 10-40%, and the molar proportion of ethylene glycol in the alcohol component is 60-90%; the molar proportion of the aromatic dicarboxylic acid in the acid component is 40-80%, and the molar proportion of the linear long-chain dicarboxylic acid in the acid component is 20-60%; different from the traditional method, the excess alcohol in the present invention is only ethylene glycol, which ensures the excess of alcohol when feeding, and the molar ratio of hydroxyl to carboxyl is greater than 1, thereby ensuring the complete esterification reaction. Since ethylene glycol is easy to evaporate in the subsequent polycondensation process, it not only promotes the growth of the polymerization chain, but also can better control the actual ratio of dicarboxylic acid (aromatic dicarboxylic acid and linear long-chain dicarboxylic acid) to diol (ethylene glycol and diol containing methyl groups in the side chain).

[0080] In an embodiment of the present invention, the condensation catalyst is selected from one of tetrabutyl titanate, antimony ethylene glycol and dibutyl tin dilaurate, preferably dibutyl tin dilaurate; the heat stabilizer is selected from one of phosphite, triphenyl phosphate, antioxidant 168 and antioxidant 1010, preferably triphenyl phosphate.

[0081] In an embodiment of the present invention, by nuclear magnetic resonance hydrogen spectrum ( 1 H-NMR) was used to qualitatively and quantitatively analyze the products.

[0082] The invention adjusts the molecular structure and performance of solvent-based amorphous polymer copolyester by introducing specific comonomers during the synthesis process. Adding diols with side chain substitutions into the polymerization reaction can synthesize resins with good solubility, flexibility and high transparency. The synthesis method of the invention is simple, the raw material cost is low, the process is pollution-free, and the application scope of domestic copolyester synthesis in the field of adhesives is broadened.

[0083] The copolyester of the present invention is a saturated polyester resin with a high number average molecular weight (up to 30,000-45,000 Da), and exhibits high tensile strength and elongation at break. The substrate coated with the copolyester can obtain excellent mechanical strength and wear resistance, thereby effectively extending the service life of the product.

[0084] In the synthesis process of the copolyester of the present invention, the even-numbered linear long-chain dibasic acid monomer has a significant effect on the softening degree of the polymer, but has no significant improvement on the solubility. Therefore, it is speculated that the solubility of the copolyester is mainly affected by the diol monomer with a side chain containing methyl.

[0085] The reason why the copolyester of the present invention has an amorphous morphology is as follows: when multiple monomers are copolymerized, the random arrangement of different structural units in the molecular chain will hinder the stacking of chain segments, thereby inhibiting crystallization. The amorphous morphology of the copolyester is derived from the difference in symmetry of the monomer structure, the random distribution of the copolymer units and the spatial hindrance of the side chains. These factors jointly inhibit the regular arrangement of the molecular chains.

[0086] The reason why the copolyester of the present invention has high transparency is as follows: the amorphous material lacks grain boundaries and defects in the crystal structure, which reduces light scattering, so that the copolyester of the present invention exhibits high transparency.

[0087] The reasons why the copolyester of the present invention has good adhesion are as follows: ① Monomers with side chains (such as methyl groups) will destroy the regularity of the molecular chain, form a branched structure, and increase the flexibility of the molecular chain. This structure makes it easier for the polymer to form physical entanglement with the substrate surface, thereby enhancing the mechanical interlocking effect; ② Forming an amorphous structure. Amorphous polymers have higher chain segment mobility, can better wet the substrate surface, reduce interface defects, and enhance adhesion strength.

[0088] The reasons why the copolyester of the present invention has good film-forming properties are as follows: the introduction of monomers with side chains (such as diols with methyl groups in the side chains) improves the solubility of the copolyester in common organic solvents, making it easy to flow and evenly spread on the surface of the substrate after dissolution.

[0089] The solvent-based amorphous polymer copolyester provided in the embodiment of the present invention can be used to prepare adhesives or film-forming materials.

[0090] The performance test standards of the present invention are as follows:

[0091] (1) Testing standards for molecular weight and dispersity

[0092] The molecular weight of the copolyester was tested by gel permeation chromatography (GPC). The test conditions were as follows: the copolyester sample was dissolved in chromatographic grade tetrahydrofuran to prepare a solution with a concentration of 1.5 mg / mL. The Alliancee2695 gel permeation chromatograph from WATERS, USA, was used. The mobile phase was tetrahydrofuran, the flow rate was 1.0 mL / min, the injection volume was 50 μL, the standard sample was narrow-distribution medium molecular weight polystyrene, the weight average molecular weight range was 266~125000Da, and the column temperature and detection temperature were both 35°C. The molecular weight and polydispersity index of the copolyester sample were determined.

[0093] (2) Test standards for copolyester structures

[0094] The structure of the copolyester was characterized by nuclear magnetic resonance spectroscopy. The sample was dissolved in tetrahydrofuran and the -1 The scan was performed in the wavenumber range with a resolution of 4 cm -1 .

[0095] (3) Test standards for copolyester crystallinity

[0096] The crystallinity of the copolyester was tested by X-ray diffractometer (XRD): the scanning angle range was 3-50 degrees.

[0097] (4) Test standard for light transmittance of copolyester

[0098] According to GB / T 2410-2008 / ASTM D1746-23, the prepared copolyester product is first cast by solution to obtain a 200-micron film, and the transmittance of different copolyester products is measured by reflection-transmission method at a specific wavelength (such as 550nm) using an ultraviolet-visible spectrophotometer (UV-vis). This standard is applicable to the transmittance detection of transparent plastics such as films and sheets.

[0099] (5) Test standards for thermal properties of copolyesters

[0100] The glass transition temperature was tested by differential scanning calorimetry (DSC) according to GB / T19466.2-2004. The sample test temperature was set at -20~80℃ in N2 atmosphere, and the heating and cooling rate was 10℃ / min.

[0101] The thermal stability was tested by a thermogravimetric analyzer (TGA) according to SN / T 3003-2011. The test temperature was set from room temperature to 600°C in a high-purity N2 atmosphere, with a heating and cooling rate of 10°C / min.

[0102] (6) Test standards for tensile strength and elongation at break

[0103] The tensile strength and elongation at break of the copolyester were tested in accordance with GB / T 1040.2-2022. The copolyester product was hot pressed into dumbbell-shaped specimens that met the requirements of GB / T528, and the tensile speed of the universal tensile machine was set to 50 mm / min.

[0104] (7) Test standards for average peel force and peel strength

[0105] The average peel force and peel strength of the copolyester were tested in accordance with GB / T 2792-2014. The polyester dissolved in an organic solvent was evenly coated on an aluminum foil, then hot-pressed, and finally cut into strips with a thickness of about 2.0 mm and a width of about 25 mm. The peeling speed of the electronic peel tester was set to 300 mm / min.

[0106] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0107] All raw materials used in the examples of the present invention are commercially available.

[0108] It should be pointed out that the matters not described in detail in the present invention are conventional operating means in the art and are not the focus of the present invention.

[0109] The technical solution of the present invention is further illustrated by the following embodiments.

[0110] Comparative Example 1

[0111] This comparative example provides a method for preparing a copolyester, and the specific method is:

[0112] (1) Preprocessing stage

[0113] Under normal pressure, nitrogen is first introduced to remove oxygen from the reaction device. According to the dosage shown in Table 1, terephthalic acid, isophthalic acid and adipic acid are added to the reactor, and the mechanical automatic stirrer is started, and the stirring speed is set to 100 rpm. Subsequently, ethylene glycol and 1,3-propylene glycol are added in sequence until the raw materials are fully mixed. Next, dibutyltin dilaurate is added dropwise as a catalyst, and triphenyl phosphate is added dropwise as a thermal stabilizer. After the addition is completed, the reflux condenser is started and the device is replaced with nitrogen three times. Then, the electric heating jacket is turned on to heat the temperature to 80°C and maintained for 10 minutes.

[0114] (2) Esterification reaction stage

[0115] The temperature of the heating mantle was gradually raised to 230°C (i.e., the esterification reaction temperature was set to 230°C), and nitrogen was used to purge to remove the water and by-products generated during the reaction. The esterification process was temperature-monitored by a fractionating column, and the column top temperature was set to the system steam temperature, which was maintained between 70°C and 105°C. When the reaction system gradually changed from turbid to clear and transparent, it was considered to have reached the clear point of the esterification reaction. When the column top temperature dropped below 60°C and the amount of distilled water reached more than 95% of the theoretical water output, the esterification reaction was completed. At the same time, the distillate was collected, its state was recorded, and gas chromatography (GC) was performed to determine the amount of reaction water.

[0116] (3) Polycondensation reaction stage

[0117] After the esterification reaction is completed, the reaction temperature is kept constant, and a diaphragm pump is used to extract the reaction system under low vacuum to prevent the liquid esterification in the three-necked flask from boiling. Gradually increase the vacuum degree to 50 Pa, keep the temperature of the heating jacket at 240°C, and then use a vacuum oil pump to continuously extract ethylene glycol and oligomers. When the reaction system becomes viscous and the molecular weight gradually increases, the polycondensation reaction time is controlled to be 3 hours. After the reaction is completed, stop heating and stirring, and turn off the vacuum pump. Subsequently, the obtained polycondensation product is quickly poured into water while hot to obtain a copolyester product ①, whose structural formula is: . At the same time, collect the distillate and record its status.

[0118] Example 1

[0119] This embodiment provides a method for preparing a solvent-based amorphous polymer copolyester, and the specific method is:

[0120] (1) Preprocessing stage

[0121] Under normal pressure, nitrogen is first introduced to remove oxygen from the reaction device. According to the dosage shown in Table 1, terephthalic acid, isophthalic acid and adipic acid are added to the reactor, and the mechanical automatic stirrer is started, and the stirring speed is set to 100 rpm. Subsequently, ethylene glycol and 2-methyl-1,3-propanediol are added in sequence until the raw materials are fully mixed. Next, dibutyltin dilaurate is added dropwise as a catalyst, and triphenyl phosphate is added dropwise as a thermal stabilizer. After the addition is completed, the reflux condenser is started and the device is replaced with nitrogen three times. Then, the electric heating jacket is turned on to heat the temperature to 80°C and maintained for 10 minutes.

[0122] (2) Esterification reaction stage

[0123] The temperature of the heating mantle was gradually raised to 230°C (i.e., the esterification reaction temperature was set to 230°C), and nitrogen was used to purge to remove the water and by-products generated during the reaction. The esterification process was temperature monitored using a fractionating column, and the column top temperature was set to the system steam temperature, which was maintained between 70°C and 105°C. When the reaction system gradually changed from turbid to clear and transparent, it was considered to have reached the clear point of the esterification reaction. When the column top temperature dropped below 60°C and the amount of distilled water reached more than 95% of the theoretical water output, the esterification reaction was completed. At the same time, the distillate was collected, its state was recorded, and GC detection was performed to determine the amount of reaction water output.

[0124] (3) Polycondensation reaction stage

[0125] After the esterification reaction is completed, the reaction temperature is kept constant, and a diaphragm pump is used to extract a low vacuum from the reaction system to prevent the liquid ester in the three-necked flask from boiling over. Gradually increase the vacuum degree to 50 Pa, keep the temperature of the heating jacket at 240°C, and then use a vacuum oil pump to continuously extract ethylene glycol and oligomers. When the reaction system becomes viscous and the molecular weight gradually increases, the polycondensation reaction time is controlled to be 3 hours. After the reaction is completed, stop heating and stirring, and turn off the vacuum pump. Subsequently, the obtained polycondensation product is quickly poured into water while hot to obtain a copolyester product ②, whose structural formula is: . At the same time, collect the distillate and record its status.

[0126] Example 2

[0127] This embodiment provides a method for preparing a solvent-based amorphous polymer copolyester. The preparation method is the same as that of Example 1, except that 2-methyl-1,3-propanediol is replaced with neopentyl glycol. The specific amount is shown in Table 1.

[0128] The solvent-based amorphous polymer copolyester obtained in this example is recorded as copolyester product ③, and its structural formula is: .

[0129] The NMR hydrogen spectrum of the solvent-based amorphous polymer copolyester obtained in this example is shown in Figure 1 It can be seen that the peak at δ 7.26 belongs to the proton of the solvent deuterated chloroform, and the peak at δ 0 is the proton of 0.03% TMS added to the solvent, which is used for chemical shift calibration. The peak at δ 8.10 is the peak of terephthalic acid, the peaks at δ 8.69, δ 8.22 and δ 7.52 are the peaks of isophthalic acid, and the peaks from δ 2.29, δ 1.58 to δ 0.85 are the peaks of adipic acid. From the integrated area of ​​each substance, n (terephthalic acid) ∶ n (isophthalic acid) ∶ n (adipic acid) ≈ 50 ∶ 20 ∶ 30, which is similar to the dibasic acid feed ratio.

[0130] The peaks of ethylene glycol are at δ 4.69, δ 4.52 and δ 4.42, and the peaks of neopentyl glycol are at δ 4.26, δ 4.15 and δ 3.98. From the integrated areas of each substance, it can be obtained that n (ethylene glycol): n (neopentyl glycol) ≈ 65: 35, which is similar to the feed ratio of diols.

[0131] The XRD pattern of the solvent-based amorphous polymer copolyester obtained in this embodiment is shown in Figure 2 It can be observed that a broad diffraction peak appears at the position of 2θ=20°, indicating the successful synthesis of the copolyester and that the molecular structure is amorphous and belongs to a random polymer.

[0132] Comparative Example 1 and Example 1 to Example 2 are compared to explore the effect of adding fatty alcohols with the same carbon chain length and different side methyl structures on the performance of the synthesized copolyester.

[0133] Comparative Example 2

[0134] This comparative example provides a method for preparing a copolyester. The preparation method is the same as that of comparative example 1, except that 1,3-propylene glycol is replaced with 1,5-pentanediol. The specific amount is shown in Table 1.

[0135] The copolyester obtained in this comparative example is recorded as copolyester product ④, and its structural formula is: .

[0136] This comparative example is compared with comparative example 1 to explore the effect of adding fatty alcohols with different carbon chain lengths and without side methyl structures on the properties of the synthesized copolyester.

[0137] Example 3

[0138] This embodiment provides a method for preparing a solvent-based amorphous polymer copolyester. The preparation method is the same as that of Example 1, except that 2-methyl-1,3-propanediol is replaced with 3-methyl-1,5-pentanediol. The specific amount is shown in Table 1.

[0139] The solvent-based amorphous polymer copolyester obtained in this example is recorded as copolyester product ⑤, and its structural formula is: .

[0140] This example is a comparison with Comparative Example 1, Example 1 and Comparative Example 2, and explores the effect of adding fatty alcohols with different carbon chain lengths and different side methyl structures on the performance of the synthesized copolyester.

[0141] Example 4

[0142] This embodiment provides a method for preparing a solvent-based amorphous polymer copolyester. The preparation method is the same as that of Example 1, except that 2-methyl-1,3-propanediol is replaced with 2-butyl-2-ethyl-1,3-propanediol. The specific amount is shown in Table 1.

[0143] The solvent-based amorphous polymer copolyester obtained in this example is recorded as copolyester product ⑥, and its structural formula is: .

[0144] This example is compared with Example 1 to explore the effect of adding a fatty alcohol having a shorter carbon chain length but a longer side methyl structure as a diol containing a methyl group in the side chain on the properties of the synthesized copolyester.

[0145] Example 5

[0146] This embodiment provides a method for preparing a solvent-based amorphous polymer copolyester. The preparation method is the same as that of Example 2, except that the polycondensation reaction time is changed to 4 hours. See Table 1 for details.

[0147] The solvent-based amorphous polymer copolyester obtained in this example is recorded as copolyester product ⑦, and its structural formula is: .

[0148] This example is compared with Example 2, and the effect of molecular weight on the performance of the synthesized copolyester is explored by extending the polycondensation reaction time.

[0149] Example 6

[0150] This embodiment provides a method for preparing a solvent-based amorphous polymer copolyester. The preparation method is the same as that of Example 4, except that the polycondensation reaction time is changed to 4 hours. See Table 1 for details.

[0151] The solvent-based amorphous polymer copolyester obtained in this example is recorded as copolyester product ⑧, and its structural formula is: .

[0152] This example is compared with Example 4, and the effect of molecular weight on the performance of the synthesized copolyester is explored by extending the polycondensation reaction time.

[0153] The copolyesters prepared in Examples 1 to 6 and Comparative Examples 1 to 2 are all saturated polyesters.

[0154] The amount of raw materials and reaction conditions of each step of Example 1 to Example 6 and Comparative Example 1 to Comparative Example 2 are shown in Table 1.

[0155] Table 1. Raw material dosage and reaction conditions of each step of Example 1 to Example 6 and Comparative Example 1 to Comparative Example 2

[0156]

[0157] The properties of the copolyesters prepared in Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 2.

[0158] Table 2. Performance of copolyesters prepared in Example 1 to Example 6 and Comparative Example 1 to Comparative Example 2

[0159]

[0160] Note: О represents dissolved; ▲ represents partially dissolved; × represents not easily dissolved.

[0161] From the data in Table 2, it can be seen that when the alcohol components in the raw materials are ethylene glycol and diols containing methyl groups on the side chains, although high molecular weight copolyesters can be prepared, the elongation at break of the copolyesters is small or they do not have good solubility. When the alcohol components in the raw materials are ethylene glycol and diols containing methyl groups on the side chains, the copolyesters prepared not only have higher molecular weights, but also have good solubility and good mechanical properties.

[0162] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A solvent-based amorphous polymer copolyester, characterized in that: The general structure is as follows: wherein R1, R2 and R3 are independently selected from hydrogen atoms, methyl groups or long carbon chain substituents; x, y, m and n are all integers greater than 1; The number average molecular weight of the solvent-based amorphous polymer copolyester is 30,000-45,000 Da, and the polymer dispersibility index is 1.7-2.

0.

2. A method for preparing the solvent-based amorphous polymer copolyester according to claim 1, characterized in that: The following steps are involved: Aromatic dicarboxylic acid, ethylene glycol, diol with methyl groups on the side chain, linear long-chain dibasic acid, polycondensation catalyst and thermal stabilizer are added and mixed at once, and pretreated at 80°C under nitrogen protection; After pretreatment, esterification reaction is carried out at 230-240°C; After the esterification reaction is completed, the reaction temperature is kept unchanged, and the reaction system is subjected to low vacuum extraction to make the vacuum degree reach 50Pa, and the temperature is maintained at 240°C. When the reaction system becomes viscous, heating is stopped, and the product is the solvent-based amorphous polymer copolyester.

3. The method for preparing the solvent-based amorphous polymer copolyester according to claim 2, characterized in that: The general structural formula of the linear long-chain dibasic acid is: Here, y is an integer greater than 1.

4. The method for preparing the solvent-based amorphous polymer copolyester according to claim 3, characterized in that: The linear long-chain dibasic acid is selected from adipic acid, sebacic acid or C12-C18 dibasic acid.

5. The method for preparing the solvent-based amorphous polymer copolyester according to claim 2, characterized in that: The molar ratio of the alcohol component to the acid component is 1.2-1.6:1; And / or, the alcohol component is ethylene glycol and a diol having a methyl group on the side chain; And / or, the acid component is an aromatic dicarboxylic acid and a linear long-chain dibasic acid.

6. The method for preparing the solvent-based amorphous polymer copolyester according to claim 5, characterized in that: The molar proportion of the ethylene glycol in the alcohol component is 60-90%; And / or, the molar proportion of the aromatic dicarboxylic acid in the acid component is 40-80%.

7. The method for preparing the solvent-based amorphous polymer copolyester according to claim 2, characterized in that: The amount of the polycondensation catalyst added is 0.05-0.1% of the mass of the linear long-chain dibasic acid; And / or, the amount of the heat stabilizer added is 0.05-0.1% of the mass of the linear long-chain dibasic acid.

8. The method for preparing the solvent-based amorphous polymer copolyester according to claim 7, characterized in that: The polycondensation catalyst is selected from one of tetrabutyl titanate, antimony ethylene glycol and dibutyltin dilaurate; And / or, the heat stabilizer is selected from one of phosphite, triphenyl phosphate, antioxidant 168 and antioxidant 1010.

9. The method for preparing the solvent-based amorphous polymer copolyester according to claim 2, characterized in that: During the esterification reaction, a distillation column is used for temperature monitoring, and the column top temperature is set to the system steam temperature, and the system steam temperature is 70°C~105°C. When the column top temperature drops below 60°C and the amount of distilled water reaches more than 95% of the theoretical water output, the esterification reaction is completed.

10. Use of the solvent-based amorphous polymer copolyester as claimed in claim 1 in the preparation of adhesives or film-forming materials.

Citation Information

Patent Citations

  • Soft polyester fiber and preparation method thereof

    CN108048940A

  • Saturated polyester copolymer as well as preparation method and application thereof

    CN114466880A

  • PETG copolyester and synthetic method for improving transparency of PETG copolyester

    CN117567733A

  • Modified copolyester material as well as preparation method and application thereof

    CN119264402A

  • Amorphous polyester composition and preparation method and application thereof

    CN105778065A